Integrating Maqāṣid al-Sharī‘ah into Contemporary Islamic Curriculum Design for Sustainable Educational Development Goals - Husna Husna; Mahmoud Abdullah; Helene Knudstad; Md. Sultan Mahmud; Khalid Abdullah Al Muzaini (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to examine the integration of Maqāṣid al-Sharī‘ah into contemporary Islamic curriculum design as a strategic framework for achieving Sustainable Educational Development Goals (SEDGs). The increasing complexity of global challenges, including digital transformation, environmental degradation, social inequality, moral crises, and the demands of sustainable development, requires Islamic education to adopt a more holistic and future-oriented educational paradigm. Employing a qualitative library research approach, this study analyzes recent scholarly literature, and policy documents, The findings reveal that the fundamental objectives of Maqāṣid al-Sharī‘ah namely the preservation of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl) demonstrate substantial alignment with contemporary educational sustainability principles, particularly those embodied in Sustainable Development Goal 4 concerning quality education. The study further identifies that the integration of maqāṣid into curriculum design can be operationalized through curriculum objectives, learning outcomes, pedagogical approaches, authentic assessment, ethical digital literacy, environmental education, and character development. The novelty of this research lies in proposing a conceptual framework that systematically links the dimensions of Maqāṣid al-Sharī‘ah with Sustainable Educational Development Goals, thereby creating a holistic, adaptive, and value-oriented model of Islamic curriculum development. The study concludes that maqāṣid-based curriculum design offers a transformative educational approach capable of promoting human flourishing, social justice, ethical responsibility, and sustainable development while maintaining the normative foundations of Islamic education